BUYING DECISION OF PT INTAN PARIWARA JUNIOR HIGH SCHOOL BOOK IN SURAKARTA 2020 - Joko Siswanto; Bambang Mursito; Istiatin Istiatin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This research aims to determine the simultaneous or partial effect of product innovation, price, promotion and brand image variables on purchasing decisions of PT Intan Pariwara Junior high School book in Surakarta area. This research method uses a quantitative research design. The population in this study were junior high school teachers in Surakarta City who used books published by PT Intan Pariwara. The sampling technique used in this research is Simple Random Sampling technique with a sample size of 100 respondents. Collecting data by using a questionnaire. The data analysis technique used was statistical analysis, namely multiple linear regression, F test, t test, and the coefficient of determination. The results showed that product innovation, price, promotion and brand image simultaneously and significantly influenced purchasing decisions of PT Intan Pariwara Junior high School book in Surakarta area. Variables that product innovation, price, promotion and brand image affect the decision to stay. Suggestions from this research, PT Intan Pariwara continues to improve product innovation, price, promotion and existing brand image, so that it will make purchasing decisions from consumers will also increase and become better than before. Keywords: Purchase Decision, Product Innovation, Price, Promotion, Brand Image